The Distribution of Zakat Funds by Bayt al-Māl for Disaster Relief: A Review Based on the Principle Taṣarruf al-Imām ‘alā ar-Ra‘iyyah Manūṭun bi al-Maṣlaḥah - Riski, Niara; Mawar, Sitti; Jalil, Husni A (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
Disaster management is a key responsibility of the government, which must be carried out in a structured, coordinated, and professional manner to achieve public welfare. In Islam, zakat functions not only as an act of worship but also as a socio-economic instrument. It aims to reduce poverty and economic inequality, which, if left unaddressed, can undermine human dignity, security, and social well-being. Zakat promotes values such as equality, cooperation, and compassion, and its distribution is managed by authorized institutions, including Baitul Maal. This study examines the legal basis for the distribution of zakat funds for disaster relief, grounded in the Islamic legal principle Taṣarruf al-Imām ‘alā ar-Ra‘iyyah Manūṭun bi al-Maṣlaḥah, which means that a leader’s policies must prioritize the public interest (maṣlaḥah). Employing a normative legal method with a conceptual and literature-based approach, this research utilizes Islamic legal analysis grounded in the principles of fiqh and the maqāṣid al-sharī‘ah. The findings reveal that while the allocation of zakat for disaster response is not explicitly mentioned in Islamic scripture (naṣṣ shar‘ī), it is permissible under specific conditions. In times of disaster, it becomes the duty of the ruler to protect the people, both in their worldly and spiritual affairs. Based on this principle, allocating zakat for disaster relief is considered lawful in Islam, particularly when it serves the public good. Therefore, Baitul Maal’s role in channeling zakat for disaster management is consistent with Islamic law and reflects the broader objective of promoting societal welfare.